The competitiveness of elite gymnasts during the Olympic cycle amid changes to competition rules - Smirnova, N.N.; Somkin, A.A.; Muhamedzyanov, R.R.; Novikova, A.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to determine the impact of the new Competition Rules for men’s artistic gymnastics for the 2025–2028 Olympic cycle on results at continental championships and the World Championships. Methods and structure of the study. The first stage involved analysing changes to the Competition Rules for men’s artistic gymnastics for 2025–2028 compared with the previous Olympic cycle. The second stage involved an analytical comparison of the results of leading gymnasts following the XXXIII Olympic Games in Paris and the 2025 World Championships. The third stage involved determining the competitiveness of Russian gymnasts following their admission to International Gymnastics Federation tournaments under neutral status. Results and conclusions. It has been established that the gymnasts from the top teams at the 2024 Paris Olympics remain leaders in the post-Olympic year. They secured leading positions at continental championships and won a total of six gold medals out of seven at the 2025 World Championships. The modernisation of the competition rules for the 2025–2028 Olympic cycle has led to increased competition between elite gymnasts and less high-level athletes; however, the D score for programme difficulty continues to make a significant contribution to victory. Russian gymnasts managed to win one medal at the World Championships – a bronze for D. Marinov on the parallel bars – whilst demonstrating the team’s high potential in the fight for victory and podium places at the next World Championships and the 2028 Olympics in Los Angeles.